Metric properties of the portuguese version of the apathy evaluation scale - Caeiro,Lara (2012)
The clinical-rated and self-rated versions of the Apathy Evaluation Scale are validated for English language. The Apathy Evaluation Scale is useful to characterize and quantify apathy. We analyzed the metric properties of the Portuguese version of the Apathy Evaluation Scale-Clinical and of a new 10-item short version of the clinical-rated and self-rated versions Apathy Evaluation Scale. We included, 156 healthy participants, 40 healthy elderly participants, 21 patients with dementia, and 21 patients with depression, comprising a sample of 238 individuals. We studied reliability using Cronbach Alpha (a) and Split-half method, and construct validity using principal component analysis with Varimax rotation. The clinical-rated and self-rated Portuguese versions of the AES are valid instruments to measure apathy in Portuguese speaking individuals. Both the clinical-rated and the self-rated versions Apathy Evaluation Scale can be used instead of the long versions of the Apathy Evaluation Scale.